Administrative Burden in the Regional Revenue Management Agency (Bapenda) of Central Java Province, Indonesia - Azani, Tiara; Diandra Kania Avriella Prastia (Arkus, 2024)
This research focuses on the impact of public services on the administrative burden at the Regional Revenue Management Agency of Central Java Province. Apart from that, this research also aims to identify the obstacles and innovative solutions faced in this context. The research method applied uses a qualitative and descriptive approach. Data was collected through observation, interviews, and documentation. The findings from this research reveal that the administrative burden on Bapenda can be divided into two, namely internal and external. Bapenda responded to this challenge by implementing innovations, such as the New Sakpole, increasing the level of transparency through PPID, and carrying out tax outreach activities.